ANALISIS PEMBERDAYAAN EKONOMI MASYARAKATMELALUI USAHA BUDIDAYA JAMUR TIRAM DESATLOGOSARI BONDOWOSO - Ahmad Fadorosid Pamungkas; Lusi Endang Sri D; Agusti Agusti (MANAJEMEN, 2025)
Community empowerment is an economic development concept that encompasses community values to build a new paradigm in people-centered, participatory development. With community economic empowerment, it is hoped that the community's life can be improved towards a better life, including basic needs, self-esteem, and freedom. Therefore, the minimum objective of community economic empowerment must prioritize what is referred to as absolute necessities, the minimum requirements to meet basic needs and  essential requirements. This study aims to describe and analyze the process of community economic empowerment in Tlogosari Village, Bondowoso. This study employs a qualitative research method with a descriptive approach. The techniques used in data collection are observation, interviews, and documentation. Data analysis uses the steps of data reduction, data presentation, and drawing conclusions. The results of the study show that the economic empowerment of the community carried out by the Oyster Mushroom Home Industry is running well. The community of Tlogosari Village has experienced economic improvement, especially for members who have joined the group. This can be seen in various aspects, such as 1) the ownership of their own mushroom houses, 2) the expansion of the business through efforts to enlarge the mushroom houses, 3) increased concern for the community through mushroom cultivation training programs, and 4) increased self-reliance with the emergence of a desire to own their own production tools, leading to greater efficiency and improved results. However, there are still unmet needs, such as the lack of government involvement in the empowerment process, both in terms of activities and meeting needs, resulting in the program not being fully realized. The current solution being pursued is to request production equipment assistance from the government, with the hope that oyster mushroom cultivation activities can be carried out to their full potential.